A Quality Improvement Study Using Fishbone Analysis and an Electronic Medical Records Intervention to Improve Care for Children With Asthma. (January 2014) - Gold, Jonathan; Reyes-Gastelum, David; Turner, Jane; ,; Davies, H. Dele
Despite expert guidelines, gaps persist in quality of care for children with asthma. This study sought to identify barriers and potential interventions to improve compliance to national asthma prevention guidelines at a single academic pediatric primary care clinic. Using the plan-do-check-act (PDCA) quality improvement framework and fishbone analysis, several barriers to consistent asthma processes and possible interventions were identified by a group of key stakeholders. Two interventions were implemented using the electronic medical record (EMR). Physician documentation of asthma quality measures were analyzed before intervention and during 2 subsequent time points over 16 months. Documentation of asthma action plans (core group P < .001, noncore group P = .004) and medication counseling (core group P < .001, noncore group P < .001) improved substantially by the third time point. A systematic approach to quality improvement using PDCA and fishbone analysis in conjunction with embedded EMR tools can improve asthma care in a pediatric primary care setting.